PENGAYAAN MODUL Salmonella sp PADA TELUR BEBEK (Anas platyrhynchos) PADA MATERI EUBACTERIA SMA KELAS X - Rafiqa Ilma Dini; Irda Sayuti; Zulfarina Zulfarina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study was conducted to use the results of the Salmonella sp test on duck eggs as a module design for the enrichment of eubacteria material for class X SMA in March-April 2020. This research was conducted in 3 stages, namely the analysis of the potential development of eubacteria teaching materials for class X SMA , and development. This research was conducted in the laboratory of the Faculty of Teacher Training and Education, University of Riau Pekanbaru. Based on the potential analysis, the research results can be used as a module design for the enrichment of eubacteria material for class X SMA. The development of the learning module includes the Analysis, Design and Development stages (prototype 1), with a module structure consisting of a cover, foreword, a table of contents, a list of pictures, a curriculum level, instructions for using the module, an introduction, learning activities, exercises, summaries, tests formative, feedback, follow-up, formative test answer keys, bibliography and glossary.Key Words: Salmonella sp, Modul, Enrichment.